Patients' and providers' perspectives on non-urgent egg freezing decision-making: a thematic analysis - Leah Drost; E. Shirin Dason; Jinglan Han; Tanya Doshi; Adena Scheer; Ellen M. Greenblatt; Claire A. Jones (BMC, 2023)
Abstract Background The decision to undergo non-urgent egg freezing (EF) is complex for patients and providers supporting them. Though prior studies have explored patient perspectives, no study has also included the separate perspectives of providers. Methods This qualitative study involved semi-structured individual interviews exploring the decision to undergo EF. Participants included patients considering EF at one academic fertility clinic and providers who counsel patients about EF from across Canada. Data analysis was accomplished using thematic analysis. Data saturation was met after interviewing 13 providers and 12 patients. Findings Four themes were identified and explored, illuminating ways in which patients and providers navigate decision-making around EF: (1) patients viewed EF as a 'back-up plan' for delaying the decision about whether to have children, while providers were hesitant to present EF in this way given the uncertainty of success; (2) providers viewed ovarian reserve testing as essential while patients believed it unnecessarily complicated the decision; (3) patients and providers cited a need for change in broader societal attitudes regarding EF since social stigma was a significant barrier to decision-making; and (4) commonality and peer support were desired by patients to assist in their decision, although some providers were hesitant to recommend this to patients. Conclusions In conclusion, the decision to undergo EF is complex and individual patient values play a significant role. In some areas, there is disconnect between providers and patients in their views on how to navigate EF decision-making, and these should be addressed in discussions between providers and patients to improve shared decision-making.